Development of Mathematics Worksheets Based on the PBL Model Integrated with Local Wisdom to Improve 4C Skills of Fifth Grade Students at Public Elementary Schools in Air Hangat Timur District - Tiara Monaliza; Hafiz Hidayat; Alfroki Martha (Journal of Educational Sciences, 2026)
This study focused on developing mathematics student worksheets (LKPD) using the Problem-Based Learning model combined with Kerinci local wisdom, aiming to strengthen the 4C skills of fifth-grade elementary students. The research followed the 4D development model, which includes defining, designing, developing, and disseminating the product. Participants were fifth-grade students from public elementary schools in Air Hangat Timur District. Data were collected through expert evaluations, teacher and student questionnaires, classroom observations, and tests measuring 4C skills. The data were then analyzed descriptively using both qualitative and quantitative methods. Results showed that the worksheets were highly valid, with an average score of 87.8%, and highly practical, with scores of 92.5% from teachers and 83.6% from students. The worksheets also proved effective in enhancing 4C skills, with average N-gain scores of 73.68% for critical thinking, 61.25% for creative thinking, 66.54% for communication, and 56.95% for collaboration. These findings indicate that PBL-based mathematics worksheets integrated with Kerinci local wisdom are practical and effective tools for nurturing 21st-century skills in students.